2001
DOI: 10.1074/jbc.m005417200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of RNA Polymerase III Transcription during Cell Cycle Entry

Abstract: Increased rates of RNA polymerase (pol) III transcription constitute a central feature of the mitogenic response, but little is known about the mechanism(s) responsible. We demonstrate that the retinoblastoma protein RB plays a major role in suppressing pol III transcription in growth-arrested fibroblasts. RB knockout cells are compromised in their ability to down-regulate pol III following serum withdrawal. RB binds and represses the pol III-specific transcription factor TFIIIB during G 0 and early G 1 , but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 63 publications
4
69
0
2
Order By: Relevance
“…To this end, transcript levels were compared from matched embryonic fibroblasts of wild-type and RB-knockout mice. Although tRNA gene expression is clearly elevated in the Rb À/À cells, as demonstrated previously (White et al, 1996;Scott et al, 2001), no increase was seen in Brf1 mRNA ( Figure 6, lanes 1 and 2). Similarly, triple knockout (TKO) fibroblasts from Rb À/À p107 À/À p130 À/À mice show elevated tRNA, but normal levels of Brf1 mRNA ( Figure 6, lanes 3 and 4).…”
Section: Variable Expression In Cervical Cells Of Mrnas Encoding Tfiimentioning
confidence: 51%
See 1 more Smart Citation
“…To this end, transcript levels were compared from matched embryonic fibroblasts of wild-type and RB-knockout mice. Although tRNA gene expression is clearly elevated in the Rb À/À cells, as demonstrated previously (White et al, 1996;Scott et al, 2001), no increase was seen in Brf1 mRNA ( Figure 6, lanes 1 and 2). Similarly, triple knockout (TKO) fibroblasts from Rb À/À p107 À/À p130 À/À mice show elevated tRNA, but normal levels of Brf1 mRNA ( Figure 6, lanes 3 and 4).…”
Section: Variable Expression In Cervical Cells Of Mrnas Encoding Tfiimentioning
confidence: 51%
“…To test this, we investigated whether raising the level of Brf1 can stimulate transcription of tRNA and 5S rRNA genes in cervical cells. Previous work showed that pol III transcription increases markedly at the G1/S phase transition due to a marked increase in TFIIIB activity as it dissociates from RB and p130 (White et al, 1995b;Scott et al, 2001). We therefore examined the response to Brf1 in both G1 and S phases.…”
Section: Brf1 Is a Limiting Factor For Pol III Transcription In Cervimentioning
confidence: 99%
“…Inactivation of RB will therefore derepress TFIIIB and allow increased rates of pol III transcription. This was demonstrated clearly with fibroblasts from RB-knockout mice, which show substantially elevated synthesis of tRNA and 5S rRNA when compared to matched wild-type cells (White et al, 1996;Scott et al, 2001). RB is expressed ubiquitously in mammals, and it is believed that RB function must be compromised for a cancer to develop (Weinberg, 1995).…”
Section: Derepression Of Tfiiibmentioning
confidence: 86%
“…Again, this reflected a specific increase in the levels of mRNAs encoding all five subunits . The mechanisms responsible for raising TFIIIC2 expression have yet to be determined, but they do not seem to reflect a simple response to accelerated proliferation Scott et al, 2001).…”
Section: Overexpression Of Pol III Transcription Factors In Transformmentioning
confidence: 99%
“…G0 cells can be distinguished from those in G1 by their diminished RNA content, which reflects diminished production of ribosomal RNAs and tRNAs (Lajtha, 1963;Ladd et al, 1997;Ren and Rollins, 2004). Pocket proteins may contribute to the G0 state by repressing ribosomal RNA and tRNA gene expression, whereas pocket protein phosphorylation may restore ribosomal RNA and tRNA levels to effect the G0-G1 transition (Cavanaugh et al, 1995;White, 1997;Hannan et al, 2000;Scott et al, 2001).…”
Section: Pocket Protein Regulation Of the G0-g1 Transitionmentioning
confidence: 99%